Faktor-faktor yang Berhubungan dengan Konsumsi Sayur pada Anak Prasekolah Perkotaan di Indonesia: Factors Associated with Vegetable Consumption among Urban Indonesian Preschool Children - Herni Dwi Herawati; Winda Irwanti; Siska Ariftiyana; Effatul Afifah; Nurja Swastir; Irma Manilet; Eska Prasetyowati; Yuyun Tuarita (Universitas Airlangga, 2026)
Background: Low vegetable consumption has been identified as a risk factor for the development of obesity. Several studies have demonstrated that vegetable consumption can have a protective effect against chronic diseases and support weight management. According to the 2018 Basic Health Research, the average vegetable intake among Indonesia children was only 72.2 grams per day, far below the recommended 300 grams. Objectives: This study aimed to determine factors associated with vegetable consumption among urban Indonesian preschool children. Methods: A cross-sectional design with 181 children selected using probability proportional to size sampling based on inclusion and exclusion criteria. Daily vegetable consumption was assessed using a semi-quantitative food frequency questionnaire (SQ-FFQ). Other variables included availability of vegetables at home, maternal knowledge, age at first vegetable introduction, parental eating behavior (assessed using the parental modelling of eating behavior scale/PARM), and feeding practices (measured using the comprehensive feeding practices questionnaire/CFPQ). Bivariate analysis employed chi-square and multivariable analysis used binary logistic regression. Results: Most children consume fewer vegetables, with 141 children (77.9%) exhibiting insufficient vegetable intake, while 40 children (22.1%) had adequate vegetable consumption. Bivariate analysis indicated that age at first vegetable consumption (p-value=0.012), parental eating behavior (p-value=0.032), and maternal knowledge (p-value=0.000) were significantly associated with vegetable consumption. Multivariable analysis revealed that maternal knowledge was the dominant factor (p-value=0.000; OR=0.42; 95% CI=0.016-0.108). Conclusions: There is a relationship between the age at which vegetables are first introduced, parental eating behavior, and maternal knowledge with vegetable consumption habits among urban preschool children.